Fertiliser-induced nitrous oxide emissions from vegetable production in the world and the regulating factors: A review. (July 2015) - Rezaei Rashti, Mehran; Wang, Weijin; Moody, Phil; Chen, Chengrong; Ghadiri, Hossein
Abstract: The emission of nitrous oxide (N2 O) from vegetable fields contributes to the global greenhouse gases budget. However, reliable estimation of N2 O emissions from vegetable production in the word has been lack. Vegetable cropping systems are characterised with high N application rates, irrigation, intensive production and multiple planting-harvest cycles during the year. Improved understanding of the key factors controlling N2 O production is critical for developing effective mitigation strategies for vegetable cropping systems under different climate, soil type and management practices. Based on a comprehensive literature review and data analysis, we estimated the global N2 O emission from vegetable production using seasonal fertiliser-induced emission factors (EFs) and examined the relationship of the seasonal emissions and EFs to possible controlling factors. The global average seasonal EF for vegetable fields is around 0.94% of applied N fertiliser, which is very similar to the Intergovernmental Panel on Climate Change (IPCC) annual emission factor of 1.0% for all cropping systems. The total N2 O emission from global vegetable production is estimated to be 9.5 × 10 7  kg N2 O–N yr −1, accounting for 9.0% of the total N2 O emissions from synthetic fertilisers. Stepwise multiple regression analysis on the relationships of soil properties, climatic factors and N application rates to seasonal N2 O emissions and N2 O EFs showed that N fertiliser application rate is the main regulator of seasonal N2 O emission from vegetable fields but the seasonal EFs are negatively related to soil organic carbon (SOC) content. In fields receiving ≥250 kg ha −1  N fertiliser, 67% (n = 23, P ≤ 0.01) of the variation in seasonal emissions can be explained by the combined effects of N application rate, mean water-filled pore space (WFPS) and air temperature, while 59% (n = 23, P ≤ 0.01) of the variation in seasonal EFs relates to temperature, mean WFPS and soil pH. The result also shows that in vegetable fields with mean seasonal air temperature higher than 14 °C, increases in SOC decrease the seasonal EF and total N2 O emissions from fertiliser N. Highlights: Factors regulating N2 O emissions and emission factors in vegetable fields are summarised. Vegetable fields do not have higher N2 O emission factors than other cropping systems. Global seasonal emission factor of vegetable fields is 0.94% of applied N fertiliser. Vegetable fields emit 9.0% of global direct N2 O emissions from synthetic fertilisers. Air temperature, soil moisture and pH control emission factor at high N application.